Knowledge and participation in exercise and physical activity among pregnant women in Ho, Ghana - Asante, Drusilla Obenewaa; Osei, Francis; Abdul-Samed, Fridaus; Nanevie, Victoria Dzifa (Frontiers in Public Health, 2022)
Background: Physical activity (PA) and exercise have been identified to improve the general fitness and health. Although, the pregnancy physical activity questionnaire (PPAQ) has been validated for use in assessing PA in pregnant women. However, understanding the knowledge and participation levels of PA in pregnant women in the underdeveloped regions of Ghana is of clinical relevance to foster education and promotion of PA. In Ghana, pregnant women believe the “myth” (mostly in rural areas and underdeveloped regions) that exercising in the first trimester might lead to miscarriage. Thus, the main objective of this study was to investigate the extent of knowledge and participation levels in PA among pregnant women in Ho, Ghana using a self-developed questionnaire which consisted of some questions adapted from the PPAQ. Methods: Seventy-seven (n = 77) pregnant women between the ages of 18 - 50 years were recruited from three hospitals across the Ho municipality of Ghana. A self-developed questionnaire which consisted of some questions taken from the PPAQ was administered to participants under the researchers’ supervision. Spearman’s correlation analysis was used to find the association between the level of participation in PA, knowledge of PA and gestational age among pregnant women. Results: From the total participants (n = 77) recruited, 57(74%) of the participants scored high in PA knowledge. Most of the participants 48 (62.3%) answered that PA promotes healthy pregnancy. Participants who reported barriers to PA during pregnancy were no exercise habits 51(66.2%), having no time 17(22.1%) and fear of miscarriage 9(11.7%). There was a significant (p < 0.05) association between the level of participation and gestational age. No significant (p > 0.05) association between the level of participation and knowledge of PA was observed. Conclusion: There is a high level of knowledge of PA among pregnant women in Ho, Ghana. However, most pregnant women rather engage in PA as their gestational age increases. Thus, to foster sustainable exercise participation during pregnancy, all healthcare providers saddled with the responsibility of providing maternal healthcare must strengthen the education and promotion of exercise and PA among pregnant women in Ho, Ghana.